A Closer Look at a Russian-Orthodox Triptych - van Tilburg, Quintly (The Rijksmuseum Bulletin, 2023)
Quintly van Tilburg examines a boxwood triptych created around 1800 in or around Moscow, donated to the museum by Baron Brakell tot den Brakell from Arnhem. The iconography represents Orthodox Christianity and corresponds to a triptych created a century later.